Satisficing Behaviour in Web Surveys: Results from a Comparison of Web and Paper Mode across Four National Survey Experiments - Clement, Sanne Lund; Severin-Nielsen, Majbritt Kappelgaard; Shamshiri-Petersen, Ditte (CHE, 2024)
Although the use of web for survey data collection has become an integral part of survey research, the quality of responses in web-based surveys is still questioned. The worry is that self-administered web-based surveys are more cognitively burdensome to respondents or encourage multi-tasking or speeding during completion, causing respondents to put lesser effort in the completion. However, most studies addressing mode differences in satisficing behaviour in web-based surveys have compared web to interviewer-administered modes, not considering that the presence of an interviewer is likely to motivate the respondent to make a greater effort. Thus, in order to contribute to more solid knowledge on the question of whether web-based surveys encourage satisficing behaviour, the present study use experimental data from four high internet coverage countries (Denmark, Iceland, Finland, and Norway) and compares web-based survey responses to paper-based responses. Findings suggest that worries over response quality in web-based surveys are unnecessary. Analyses of three different measures of satisficing behaviour in survey responses do not give any support to the assumption that respondents completing on web are more prone to satisficing behaviour.